The New Singapore Law on Antidumping and Countervailing Duties - HSU, Locknie (Institutional Knowledge at Singapore Management University, 1998)
The Countervailing and Anti-dumping Duties Act 1996 ("the Act") came into effect on 1 November 1996.1 This legislation was enacted to bring Singapore's law in relation to countervailing duties, subsidies and antidumping into conformity with requirements of the World Trade Organization (WTO) Agreements It also updates the law by repealing the outmoded Customs (Subsidies and Anti-dumping) Act. The new rules and procedures in the Act are meant to "give added assurance and certainty to the local and foreign parties concerned whenever an action is instituted."In addition to the Act, detailed regulations have also been passed. The Act follows the basic requirements of the Antidumping and Subsidies Agreements closely, but also includes supplementary provisions. Part 11 of the Act deals with the area of countervailing duties in relation to subsidies. Part 111 deals with antidumping. Most of the provisions in Part 11 have parallel, if not identical, provisions in Part 111. Many of the provisions are adapted from those in Malaysia's Countervailing and Anti-Dumping Duties Act 1993 ("the Malaysia Act"). This article will examine the administration of the Act, the antidumping and subsidy provisions, the review process and a number of other general issues.